Recycling Program: Turning Waste into Useful and Valuable Products for Communities and Entrepreneurs - Kaidah, Sri; Suprapto, Suprapto (Transpublika Publisher, 2025)
Waste recycling programs have become crucial due to the mounting waste problems that threaten the environment, public health, and the sustainability of natural resources. This program aims to transform the waste management paradigm from a linear system (disposal) to a circular economic cycle, converting waste into beneficial and economically valuable products. The main objectives include significantly reducing the volume of waste that ends up in Final Disposal Sites (TPA), increasing the availability of quality recycled raw materials, and fostering awareness and active community participation in recycling practices. The targeted outcomes include creating new jobs in the collection, processing, and marketing sectors of recycled products. Additionally, this program is expected to increase community income, particularly among entrepreneurs, through the sale of innovative and high-value recycled products. Thus, the recycling program is expected to create a sustainable ecosystem that benefits the environment, society, and the economy as a whole.